Effect of midgut proteolytic activity on susceptibility of lepidopteran larvae to Bacillus thuringiensis subsp. Kurstaki - Talaei-Hassanloui, Reza; Bakhshaei, Raziyeh; Hosseininaveh, Vahid; Khorramnezhad, Ayda (Frontiers in Physiology, 2014)
Bacillus thuringiensis (Bt) is the most effective microbial control agent for controlling numerous species from different insect orders. All subspecies and strains of B. thuringiensis can produce a spore and a crystalline parasporal body. This crystal which contains proteinaceous protoxins is dissolved in the alkaline midgut, the resulting molecule is then cleaved and activated by proteolytic enzymes and acts as a toxin. An interesting aspect of this activation process is that variations in midgut pH and protease activity have been shown to account for the spectrum of some Bt proteins activity. Thus, an important factor that could be a determinant of toxin activity is the presence of proteases in the midgut microenvironment of susceptible insects. Reciprocally, any alteration in the midgut protease composition of the host can result in resistance to Bt. Here in this paper, we reviewed this processes in general and presented our assays to reveal whether resistance mechanism to Bt in Diamondback Moth larvae could be due to the function of the midgut proteases? We estimated LC50 for both probable susceptible and resistant populations in laboratory and greenhouse tests. Then, the midgut protease activities of the B. thuringiensis ind